A serologicalsurveillance of bluetongue disease in sheep and goats in Iraq by using acompetitive ELISA Technique: Khalid H. Shlash1 , Laith MS. Abdul-Rasoul2 , Mazin M. Naji2 ,Mahir H. Hussain2 - Shlash, Khalid H. (The Iraqi Journal of Veterinary Medicine, 2012)
In this study, a sero-survillance on ovine and caprine serum samples from all over Iraqexcept the governorates of Iraqi Kurdistan region was conducted. It aimed for the detection ofspecific antibodies directed against VP7 protein - the sero-group specific antigen of bluetongue virus – by using a competitive ELISA technique.The results showed that among a totalof 3277 serum samples, 1436 samples were found to be positive forming 43.82% of totalsamples, while 1687 samples were negative with 51.48 % and 154 sample were suspiciousforming 4.69 %. The highest positive serum samples were found in Al Basrah Province(southern of Iraq) with 60.41% and in Al Anbar Province (Western of Iraq) with 61%, whilethe lowest of positive samples were found in Nineva (Northern of Iraq) with 22.35%.The results also showed a closely ratio between positive percentage of goats and sheepsamples with the positive goats serum samples ( in five provinces ) were 45 of 114 samplesrepresenting 39.47 %,while the positive sheep serum samples ( in fifteen provinces) were1391 of 3163 samples representing43.97%. Our study is complementary to the previousworks held in this field and it represents the first field serological survey for bluetongueinsheep and goats in Iraq.